Effectiveness of Blood Flow Restriction on Functionality, Quality of Life and Pain in Patients with Neuromusculoskeletal Pathologies: A Systematic Review - Reina-Ruiz, Álvaro Jesús; Martínez-Cal, Jesús; Molina-Torres, Guadalupe; Romero-Galisteo, Rita Pilar; Galán Mercant, Alejandro; Carrasco-Vega, Elio; González-Sánchez, Manuel (IOAP-MDPI, 2023)
Background: Blood flow restriction is characterized as a method used during exercise at low loads of around 20–40% of a repetition maximum, or at a low-moderate intensity of aerobic exercise, in which cuffs that occlude the proximal part of the extremities can partially reduce arterial flow and fully restrict the venous flow of the musculature in order to achieve the same benefits as high-load exercise. Objective: The main objective of this systematic literature review was to analyze the effects of BFR intervention on pain, functionality, and quality of life in subjects with neuromusculoskeletal pathologies. Methods: The search to carry out was performed in PubMed, Cochrane, EMBASE, PEDro, CINHAL, SPORTDiscus, Trip Medical Database, and Scopus: “kaatsu” OR “ischemic training” OR “blood flow restriction” OR “occlusion resistance training” OR “vascular occlusion” OR “vascular restriction”. Results: After identifying 486 papers and eliminating 175 of them due to duplication and 261 after reading the title and abstract, 50 papers were selected. Of all the selected articles, 28 were excluded for not presenting a score equal to or higher than 6 points on the PEDro scale and 8 for not analyzing the target outcome variables. Finally, 14 papers were selected for this systematic review. Conclusions: The data collected indicate that the blood flow restriction tool is a therapeutic alternative due to its effectiveness under different exercise modalities. The benefits found include decreases in pain thresholds and improvement in the functionality and quality of life of the neuro-musculoskeletal patient during the first six weeks. However, the results provided by this tool are still not clear for medium- and long-term interventions.
Keywords: Flujo sanguíneo; Blood flow restriction; Pain; Quality of life; Exercise; Neuromusculoskeletal disorders